Probing fluid flow using the force measurement capability of optical trapping - Eom, N.; Stevens, V.; Wedding, A.; Sedev, Rossen; Connor, J. (Elsevier, 2014)
Interest in microfluidics is rapidly expanding and the use of microchips as miniature chemical reactors is increasingly common. Microfluidic channels are now complex and combine several functions on a single chip. Fluid flow details are important but relatively few experimental methods are available to probe the flow in confined geometry. We use optical trapping of a small dielectric particle to probe the fluid flow. A highly focused laser beam attracts particles suspended in a liquid to its focal point. A particle can be trapped and then repositioned. From the displacement of the trapped particle away from its equilibrium position one estimates the external force acting on the particle. The stiffness (spring constant) of the optical trap is low thus making it a sensitive force measuring device. Rather than using the optical trap to position and release a particle for independent velocimetry measurement, we map the fluid flow by measuring the hydrodynamic force acting on a trapped particle. The flow rate of a dilute aqueous electrolyte flowing through a plastic microchannel (W× H × L = 5 mm× 0.4 mm × 50 mm) was mapped using a small silica particle (1 µm diameter). The fluid velocity profile obtained experimentally is in very good agreement with the theoretical prediction. Our flow mapping approach is time efficient, reliable and can be used in low-opacity suspensions flowing in microchannels of various geometries.